2012
DOI: 10.3399/bjgp12x649124
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics for acute cough: an international observational study of patient adherence in primary care

Abstract: BackgroundNon-adherence to acute antibiotic prescriptions is poorly described and may impact on clinical outcomes, healthcare costs, and interpretation of research. It also results in leftover antibiotics that could be used inappropriately. AimTo describe adherence to antibiotics prescribed for adults presenting with acute cough in primary care, factors associated with non-adherence, and associated recovery. Design and settingProspective observational cohort study in general practices in 14 European primary ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 26 publications
3
36
2
1
Order By: Relevance
“…These data are consistent with previously reported theoretical constructs and empirical data (14,21,27). Other studies found that poor adherence was associated with a higher number of daily doses of the antibiotic (16,(28)(29)(30), longer antibiotic treatment duration (25,26,28), increasing age, difficulty in buying the antibiotic, duration of treatment, difficulty with ingestion, and satisfaction with the information given by the physician (26). We found that lower adherence was a significant risk factor for poor clinical outcome.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…These data are consistent with previously reported theoretical constructs and empirical data (14,21,27). Other studies found that poor adherence was associated with a higher number of daily doses of the antibiotic (16,(28)(29)(30), longer antibiotic treatment duration (25,26,28), increasing age, difficulty in buying the antibiotic, duration of treatment, difficulty with ingestion, and satisfaction with the information given by the physician (26). We found that lower adherence was a significant risk factor for poor clinical outcome.…”
Section: Discussionsupporting
confidence: 82%
“…Few investigations have examined both adherence and clinical outcome for acute infectious diseases. One investigation found no association between clinical outcomes of cough based on patient-reported adherence (25). This lack of association may be based on the fact that antibiotics for bronchitis have no effect on clinical outcome in the majority of patients with bronchitis (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 GPs in five European countries mentioned patient demand for antibiotics as a driver for prescribing, and supported patient directed educational materials and public campaigns to reduce demand. 29 Antibiotic compliance in acute cough, recorded prospectively in patients from Cardiff and Southampton, was much lower (54% and 58%) 30 than the 75% of participants in this current study who reported finishing their antibiotic course. In contrast, an English telephone survey found that 90% of responders reported finishing their last course; 31 retrospective surveys may not be as reliable as the prospective study.…”
Section: Comparison With Existing Literaturementioning
confidence: 78%
“…Nevertheless, we should keep in mind that prescribing does not equal consumption, as was clearly shown for antibiotics prescribed for lower RTI by Francis et al. [31], and especially true in high prescribing settings.…”
Section: Discussionmentioning
confidence: 99%